FIELDING’S “AMELIA”. THEMATIC PLURALITY OF THE NOVEL - Svetlana A. Vatchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
Article deals with the attempt to describe the semantic сapacity of Fielding`s last novel “Amelia” that became the notable event in writer’s biography and remains the object of discussion among the researches starting from its first publication. Fielding was at the height of his fame as the magistrate for Westminster and Middlesex and as a celebrated novelist who was an opponent of Samuel Richardson. His novel “Tom Jones” (1749) despite some harsh criticism had been generally acclaimed. According to the title “Amelia” obviously differs from Fielding’s early novels: “Joseph Andrews”, “Jonathan Wild” and “Tom Jones”. With his central heroine Fielding has entered the territory associated with Richardson, whose distressed female characters, Pamela and Clarissa, had captured the attention of the reading public. It is well-known that Amelia Booth was modelled on Fielding’s first wife, Charlotte Craddock, while his hero, Captain Booth, was inspired be the author himself as well as his father, Lieutenant General Edmund Fielding. Trying to defend “Amelia” Fielding in the Covent-Garden Journal insists that he has followed the rules for the epic of Homer and Virgil, saying that the “learned reader will see that the latter was the noble model”. Like the “Aeneid”, “Amelia” consists of twelve books, and the opening section of the novel, set in Newgate, is a parallel to Virgil. The author being in the heyday of his glory brought before the public his new, experimental text, giving up the form of comic epic poem in prose that was immortalized in “The History of Tom Jones, a Foundling”. Denying the technique that was deeply rooted in the English prose due to the narrative skill and the omniscient author (who acted as theorist of the novel), theatrically performing the game with the reader through metanarrative, Fielding in “Amelia” prefers restrained position of the narrator using the recourses of dramatical art. Choosing the plain plot about the everyday difficulties, poverty and humiliations of a young married couple that is peculiar for European sentimentalism, Fielding – due to the thematic tightness of the novel, its allusive fullness, the ambiguity of characters, the poetics of concealment – the narrative about the life of a libertine in a family (W. Scott) presents not so much as the moral lesson for the protagonist that is guided by passions but as ethical transformation that comes with the experience of the “art of life”. In recent decades “Amelia” has been the subject of many investigations, its experimental qualities made it attractive to critics of both the development of the 18th century novel and Fielding’s career. Modern readers however, have shown less interest for the work. Critical hostility to “Amelia” often seems to imply disappointment that it is not like “Tom Jones”. “Amelia” is often called a sequel to his masterpiece “Tom Jones” (Walter Scott) but Fielding adopted a new form of verisimilitude and changed his narrative technique, setting and tone. Historians agree that “Tom Jones” is loosely an epic, with a plot drawn from romance, while “Amelia” is modelled on a classical epic – Virgil’s “Aeneid” – and effects to eschew romance (Martin Battestin, Claude Rawson, Peter Sabor, Ronald Paulson, Simon Varey). The instability of reputation of Fielding’s “Amelia” demonstrates that the novel was traditionally estimated as writer’s failure but nowadays it is viewed as complicated literary form addressed to the highbrow reader. According to Peter Sabor, “Amelia” might never become the “favourite Child” of Fielding’s readers, as it was of Fielding himself, but what remains convincing about his last and most problematic novel is its harsh, world-weary picture of a venal society. Fielding’s darkened view of the people’s community influenced the later samples of the genre and reached successful treatment of the similar themes in the English novel of the 19th century. All the more it is the universal experience of the renewal of genre poetics and the reading of “Amelia” represents Fielding’s original conception of the novel. According to the declared problem the author of the present article uses historical and literary, sociocultural and hermeneutic approaches in the synthesis with the technique of close reading